Conflicts and complements between eastern cultures and agile methods: an empirical investigation. Issue 2 (1st March 2017) - Ramesh, Balasubramaniam; Cao, Lan; Kim, Jongwoo; Mohan, Kannan; James, Tabitha L.
Abstract: Agile methods have been widely adopted around the world – particularly in the Eastern world, where cultural scripts differ from that of the West from where agile methods originated. However, there is a lack of understanding of the interplay between the basic tenets of agile methods and the Eastern cultures. This understanding is crucial for the effective use of the methods in these cultures. To examine how Eastern cultural phenomena interplay with agile methods, we followed an emic approach in a multisite case study. We examined the adaptation of agile practices in organizations in China, India, and South Korea. We developed a framework describing how Eastern cultural scripts often express the collectivist response to cultural theoretical concepts and how the cultural response interacts in complementary and conflicting ways with agile methods. To explore how conflicts are mitigated, we examined the ways organizations develop ambidextrous practices.